Revisiting euphemisation strategies for English to Indonesian subtitle context - SF. Luthfie Arguby Purnomo; Ikke Dewi Pratama; Lilik Untari; SF. Lukfianka Sanjaya Purnama; Novianni Anggraini (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2020)
Character equivalence and offensive word rank in subtitling context are understudied on the previous studies on euphemisation strategies. The exclusion of these two concerns leaves the prior constructed euphemisation strategies unable to explain how shifts on narrative identity might occur and how taboo words are functionally negotiated. In addressing this issue, the study investigates the relationship between offensive word levels with character equivalence and narrative identity, types of euphemisation strategies, and the strategies' implementation. The data were collected from the English and Indonesian versions of four films containing taboo words, which were analyzed by applying the theories of offensiveness rank by Ofcom, constructed in English as a foreign language context, and character equivalence by Petrucci. The findings indicate that offensive word translation suffers a rank shift on offensive word ranks Departing from these findings. We propose euphemisation strategies with offensive word rank and character equivalence as the primary narrative basis with mediality and subtitling standard as the primary mechanical basis. Those strategies are downgrading, degrading, sidegrading, outgrading, ingrading, and retrograding. The reasons of euphemisation strategy implementation are bipolarly divided into aesthetics and mechanics in relation to distances and perspectives of the applied offensive words.